ALC-2203, a Combination of Coptidis Rhizoma Dry Extract and Ivy Leaf 30% Ethanolic Dry Extract for Acute Bronchitis: Preclinical Pharmacology, Oral Formulation Development and Clinical Evaluation - Nakyeom Lee; Sang Young Jeong; Sang Gil Lee; Eun Byul Lee (Innovations in Acupuncture and Medicine, 2026)
Abstract Background Acute bronchitis is a common respiratory disease characterized by acute airway inflammation, requiring effective and safe anti-inflammatory therapies. ALC-2203 is a botanical drug candidate combining Coptidis rhizoma dry extract and ivy leaf (hederacoside C) ethanolic dry extract, designed to provide complementary anti-inflammatory and symptom-relieving effects. This study aimed to evaluate the preclinical anti-inflammatory efficacy of ALC-2203 in a lipopolysaccharide (LPS)-induced mouse model, develop a quality-controlled oral tablet formulation, and assess its clinical efficacy and safety in patients with acute bronchitis. Methods Preclinically, acute bronchitis was induced in ICR mice via intranasal LPS administration. ALC-2203 (20, 40, and 80 mg/kg) orally administered to evaluate inflammatory cells in bronchoalveolar lavage fluid (BALF) inflammatory cells, cytokines, and lung histopathology. A 318-mg tablet formulation was developed and validated using an HPLC method for berberine quantification. Clinically, a randomized, double-blind, placebo- and active-controlled, multicenter Phase 2 trial enrolled 168 patients who received placebo, ALC-2203-2 (low dose), ALC-2203-1 (medium dose), and the active control, ALC-2203-AC (Synatura® syrup), for 7 days. The primary endpoint was the change from baseline in the Bronchitis Severity Score (BSS) at Day 7. Results In the mouse model, ALC-2203 reduced inflammatory cells, including macrophages, neutrophils, and lymphocytes, in BALF, thereby suppressing pro-inflammatory cytokines (i.e., TNF-α, IL-1β, and IL-6) and improving pulmonary histopathology. The tablet formulation demonstrated analytical performance, including linearity (R 2 ≥ 0.999), accuracy (98–102%), and precision (%RSD < 2.0). Clinically, all groups showed improvements from baseline BSS by Day 7, but neither ALC-2203 dose demonstrated superiority over placebo for the primary endpoint. In the exploratory endpoint analysis of the BSS cough subscale, ALC-2203-2 showed a numerically greater reduction from baseline than placebo at Day 4, and a greater reduction than ALC-2203-AC at Day 4 and Day 7. However, the differences were not statistically significant. ALC-2203 was well tolerated, with no serious adverse reactions. Conclusions ALC-2203 demonstrated preclinical anti-inflammatory activity and was formulated into a quality-controlled oral tablet. Although superiority over placebo was not established for the primary clinical endpoint, exploratory findings in selected cough-related secondary outcomes and a favorable safety profile support further investigation of this agent in acute bronchitis. Trial registration ClinicalTrials.gov, NCT07061925. Graphical Abstract Preclinical and clinical pharmacology of ALC-2203 comprising Coptidis rhizoma and ivy leaf extract